2012
DOI: 10.1063/1.4755990
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some dispersion-corrected and traditional functionals with CCSD(T) and MP2 ab initio methods: Dispersion, induction, and basis set superposition error

Abstract: We compare dispersion and induction interactions for noble gas dimers and for Ne, methane, and 2-butyne with HF and LiF using a variety of functionals (including some specifically parameterized to evaluate dispersion interactions) with ab initio methods including CCSD(T) and MP2. We see that inductive interactions tend to enhance dispersion and may be accompanied by charge-transfer. We show that the functionals do not generally follow the expected trends in interaction energies, basis set superposition errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 68 publications
(34 reference statements)
3
43
1
1
Order By: Relevance
“…We have used this procedure on small systems. 21 However, TABLE V. E's (kcal/mol) for aggregation of parallel sheets and sums of pairwise interactions using DFT, MP2, and CCSD(T) with the cc-PVTZ basis set for structures of Figure 1. the small changes expected would not bring the CCSD(T) values close to the interaction energies predicted by the DFs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have used this procedure on small systems. 21 However, TABLE V. E's (kcal/mol) for aggregation of parallel sheets and sums of pairwise interactions using DFT, MP2, and CCSD(T) with the cc-PVTZ basis set for structures of Figure 1. the small changes expected would not bring the CCSD(T) values close to the interaction energies predicted by the DFs.…”
Section: Resultsmentioning
confidence: 99%
“…We have published an evaluation of the DFs compared to high level calculations for small systems that have dispersion combined with inductive interactions. 21 This report contains a comprehensive list of the database used for parameterization of the DFs. In order to further probe the local interactions that contribute to overall stabilizations of the stacked structures, we divided each structure into two parts that we considered separately: (1) the peptide backbone, and (2) the aromatic rings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…can improve the accuracy of grid based electrostatic potential methods such as CHELPG and MK [50]. Roy [26] has shown that the B3LYP functional can account for dispersion and induction interactions in intermolecular complexes as well as functionals (eg MP2) designed to treat dispersion.…”
Section: Methodsmentioning
confidence: 99%
“…The van der Waals interactions in vacuo, ΔE vdW , are then calculated from equation (2), where -van der Waals interactions‖ are defined as a global term including all forces that are not hydrogen bonding or other polar interactions. Calculating ΔE vdW is difficult, since they include multiple anisotropic forces [26], and solvents have large attenuating effects compared to those in vacuo. All water molecules in the X-ray structures were removed, since it is unknown how many, if any, water molecules dynamically interact with the tyrosine kinase, inhibitor, or tyrosine kinaseinhibitor complex.…”
Section: The Approach Taken In This Study To Examine How Possible Dismentioning
confidence: 99%